Acral Involvement of Lymphoblastic Lymphoma Revealed on FDG PET/CT. (April 2019) - Wen, Zhe; Zhuang, Hongming
Abstract : Abstract: Lymphoma rarely involves hand or foot. We presented the FDG PET/CT findings of lymphoblastic lymphoma in a 28-year-old man who had recurrent disease in many bones, including those of the hand and foot without any lymph node involvement 17 years after initial diagnosis.